Left Ventricular Morphology and Function in Female Athletes: A Meta-Analysis - Whyte, G. P.; George, K.; Nevill, A.; Shave, R.; Sharma, S.; McKenna, W. J. (International Journal of Sports Medicine, 2004)
The purpose of the present study was to examine the impact of physical training upon cardiac structure and function, and identify physiologic upper limits in female athletes. Meta-analytical techniques were applied to 13 published echocardiographic studies examining cardiac structure and function in female athletes. The study group included 890 athletes and 333 controls. For comparison of sporting discipline, studies were partitioned into 3 categories (endurance, strength/sprint, team). Significant (p < 0.05) effect sizes were observed for all structural measures between athletes and controls. Significant effect size differences existed between sporting groups for LVIDd and LVM only, with endurance and team game athletes demonstrating the largest effect sizes compared to strength trained athletes. No significant effect of training was observed for left ventricular diastolic or systolic function, with the exception of stroke volume where a significant effect size difference was observed between athletes and controls with no observed difference between sporting groups. Maximum reported upper limits for LV wall thickness and LVIDd in female athletes were 12 mm and 66 mm respectively. Chronic exercise training results in cardiac enlargement in female athletes. The nature of physiologic adaptation is similar to that observed in male athletes. LV wall thickness values greater than 12 mm in female athletes should be viewed with caution and indicate a more comprehensive evaluation to establish a physiological or pathological basis for the observed left ventricular enlargement.